Estimating The Economic Impact Of Road Accident Deaths In Uttarakhand Foothills Of Himalayas Using Direct Output Method (International Journal of Food and Nutritional Sciences, 2022)
Background: Road accidents are a leading cause of death and injury worldwide, and India is no exception. The state of Uttarakhand, situated in the foothills of the Himalayas, has a high incidence of road accidents, with a significant number of fatalities each year. In addition to the personal tragedy of lives lost, road accidents also have significant economic costs, including the loss of income and the cost of healthcare. Estimating the economic impact of road accidents is an essential step towards developing effective policies to reduce their occurrence.Methodology: This study estimates the economic impact of road accident deaths in Uttarakhand foothills of Himalayas using the direct output method. This method estimates the economic impact of an event by measuring the direct loss of output resulting from the event. In this study, we used secondary data from the Transport Research Wing and Police Records, Government of Uttarakhand with prior permission and then collected primary data from the attendants and family members of the death victims. We then calculated the economic loss in terms of medical/hospital costs, loss output costs, pain and grief costs, police and legal costs and vehicle damage costs